The Effect of Simulation Learning Strategy and Education Background on the First Learning Outcomes of Private Students Madrasah Tsanawiyah - Habib, Muhammad; Zein, Achyar; Budianti, Yusnaili (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
The purpose of this study is to determine the impact of simulation learning strategies and educational background on the learning outcomes of fiqh students at Gunung Sitoli's private madrasah tsanawiyah. The method used in this study is quasi-experimental. This method was chosen because the treatment class, both for the simulated learning class and the expository learning class, was a pre-formed class and the students being controlled had an educational background. The results of statistical analysis calculations show that there is an interaction between learning strategies and educational backgrounds, with students with a MI educational background benefiting more from simulation learning strategies than expository learning strategies, and students with an elementary education background benefiting more from expository learning strategies than simulation learning strategies.